Antitumor activity and tumor necrosis factor production of Phytolacca acinosa polysaccharides I in mice. - Zhang Jun-Ping; Qian Ding-Hua (Acta Pharmacologica Sinica, 2016)
The antitumor activities of Phytolacca acinosa polysaccharides I (PAP-I) and its effects on the induction of tumor necrosis factor (TNF) and immunological cytotoxicity of peritoneal macrophages were studied. PAP-I was given ip 5-20 mg.kg-1.d-1 x 7 d to ICR mice as priming agent with subsequent lipopolysaccharides (10 micrograms/mouse) iv for TNF production. TNF activity was measured by crystal violet staining assay using L929 cells. PAP-I showed priming activity for TNF production with hepto-splenic hyperplasia in a dose-dependent manner. The peritoneal macrophages treated with PAP-I 10 and 20 mg.kg-1 showed 67 and 74%, respectively, cytotoxicity (the control 34% cytotoxicity) against Meth A cells at effector:target = 40:1. PAP-I 10 and 20 mg.kg-1 prolonged the survival time of mice bearing ascites Meth A tumor from 21 +/- 4 to 32 +/- 10 and 38 +/- 8 d and inhibited the solid Meth A tumor growth with inhibition rate of 28.5 and 55.7%, respectively. These results suggested that the antitumor activities of PAPI were based on the activation of macrophages and induction of TNF.